Pelatihan Peningkatan Communication Skill dan Peningkatan TOEIC Mahasiswa Level D3 Teknik Mesin PSDKU Politeknik Negeri Malang di Kota Kediri - Rasyidah, Umi Imtitsal; Salim, Mochammad Abdullah; Safa’udin, Muhamad; Fanani, Ahmad Johan (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aims to improve the communication skills and TOEIC scores of D3 Mechanical Engineering students at PSDKU Politeknik Negeri Malang in Kediri City. The background of this activity is the low level of communication skills and English proficiency among engineering students, which has the potential to hinder learning and mastery of the material. The training methods used include blended learning, project-based learning, collaborative learning, and intensive TOEIC training. The participants in the training were final semester students who needed to improve their English skills. The results showed an average increase in TOEIC scores of 150 points and a significant improvement in communication skills, confidence, and readiness to enter the workforce. However, there were still obstacles in listening skills and grammar mastery. Overall, this program has proven to be effective and can be provided to other groups of students to support the improvement of graduate quality who are better prepared to face the national and international workforce.